KREATIVITAS GURU PENDIDIKAN AGAMA ISLAM DALAM UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK DI SEKOLAH - Adin (UNISAN JURNAL, 2024)
The reason for this exploration is to find out and comprehend the job of Islamic Strict Schooling Educators to expanding understudies' advantage in learning in Islamic Strict Training subjects. This examination utilized subjective exploration techniques which occurred at the Raudlatun Najah Incorporated Islamic Grade School. Analysts led organized interviews and unstructured meetings with asset people (SMPIT Islamic Strict Training educators) which were upheld by information documentation and direct perception. The discoveries in this exploration depend on the aftereffects of information examination and conversations that have been depicted in the past parts, so the ends in this examination can be planned as follows. 1. Execution of learning the board in working on the nature of graduates at the Anisya course and preparing foundation, which comprises of arranging, carrying out and assessing advancing all in all, has been completed well. 2. There are a few supporting variables for executing learning the executives in working on the nature of graduates at Raudlatun Najah Coordinated Islamic Primary School, for example, great help from the public authority, the presence of two adaptable learning programs, proficient educators, dynamic via web-based entertainment, great and complete offices, as well as an essential area. Factors hindering the execution of learning the board in working on the nature of graduates at the Raudlatun Najah Coordinated Islamic Primary School include: there are still educators who are not yet guaranteed, the ages and foundations of understudies are different, there are conflicting understudies. following preparation to the end, and absence of understudy discipline..